Second Iteration of Slotted Fractal Log Periodic Dipole Antenna for UHF Digital TV Band Application (ELEKTRIKA- Journal of Electrical Engineering, 2021)
This paper discusses the simulations and measurements of the antenna with and without slot implementation in terms of reflection coefficient (S11) and radiation pattern. The slot implementation on each of the radiating elements on the 2nd iteration log periodic fractal Koch antenna (LPFKA) was described in this paper. This method is utilised to reduce the antenna's size while also preventing the lower designated frequencies from shifting to the higher band as the iteration increases. The antenna is designed to test and observe performance in the Ultra High Frequency (UHF) band, which ranges from 0.5 GHz to 3.0 GHz. Computer Simulation Technology (CST) software is used to design and model the antenna, which was then built using the wet etching technique. The antenna's substrate is made of FR-4 laminated board with a dielectric constant of 4.6, tangent loss of 0.019, and a thickness of 1.6mm. The results demonstrate good agreement, with a steady radiation pattern over the operational bandwidth and a reflection coefficient of less than -10 dB for the frequency range of interest. The antenna is being tested with Digital TV decoder and the result is observed towards the picture of the Digital TV.
Keywords: Fractal Koch geometry, Log periodic antenna, slotted technique, UHF band